Folk classification and traditional uses of Cyperus esculentus, a neglected and underutilized species in Benin - Vidédji Naéssé ADJAHOSSOU; Dossou Seblodo Judes Charlemagne GBEMAVO; SAMUEL ABIDJA; Judicaël LALY; Ahodpnissou Anicet GBAGUIDI; Alexandre DANSI ANAGONOU (Society for Indonesian Biodiversity, 2021)
Abstract. Adjahossou VN, Gbemavo DSJC, Abidja S, Laly J, Gbaguidi AA, Anagonou AD. 2021. Folk classification and traditional uses of Cyperus esculentus, a neglected and underutilized species in Benin. Biodiversitas 22: 2972-2979. The sweet pea or tigernut (Cyperus esculentus L.) has very high potential to be developed but is considered a neglected and underutilized plant in Benin. The current study aims to investigate the indigenous knowledge related to local diversity, production and uses of various landrace types of tigernut grown in its production areas in Benin. Using Participatory Research Appraisal (PRA) method, we surveyed 113 tigernut farmers in different regions of production in Atacora Department, Benin. Univariate statistics were performed to describe and compare tigernut farmers' responses on botanical and agronomic criteria. We found that the tigernut farmers in the studied area distinguished three landraces of C. esculentus. Two landrace types produced yellow-skinned tubers and the other produced black-skinned tubers. Economic value, agro-morphological traits and organoleptic quality were the criteria considered by the farmers when choosing the type of landrace to cultivate. According to the farmers, the attacks of the tubers by earthworms and termites constituted the main constraints of the production of tigernut. Local people used the species mainly for food, while small proportion was for medicine (e.g., for aphrodisiac) and soil fertilization purposes. This study implies that C. esculentus in Benin deserves better attention to be conserved and developed.